Antigen Presentation in the CNS by Myeloid Dendritic Cells Drives Progression of Relapsing Experimental Autoimmune Encephalomyelitis - MILLER, STEPHEN D.; McMAHON, EILEEN J.; SCHREINER, BETTINA; BAILEY, SAMANTHA L. (Annals of the New York Academy of Sciences, 2007)
:  Chronic progression of relapsing experimental autoimmune encephalomyelitis (R‐EAE), a mouse model of multiple sclerosis (MS), is dependent on the activation of T cells to endogenous myelin epitopes, that is, epitope spreading. This review focuses on the cellular and molecular mechanisms underlying the process of epitope spreading. Surprisingly, activation of naïve T cells to endogenous myelin epitopes in SJL mice undergoing R‐EAE occurs directly in the central nervous system (CNS), a site generally perceived to be immunologically privileged. Determination of the antigen presentation capacity of antigen‐presenting cell (APC) populations purified from the CNS of mice with established R‐EAE shows that peripherally derived CD11b+CD11c+CD45hi myeloid dendritic cells (mDCs) most efficiently present endogenous myelin antigens to activate both preactivated effector myelin‐specific T cells and naïve T cells. The mDCs, which drive epitope spreading, preferentially polarize pathogenic Th17 responses correlating with their enhanced expression of TGF‐β1, IL‐6, and IL‐23. Both B220+CD11c+ plasmacytoid (pDCs) and CD8α+CD11c+ (CD8 DCs) were superior to CD11b+CD11c–CD45hi macrophages, but less efficient than mDCs at presenting endogenous peptide to induce Th17 cells. In contrast, CNS‐resident CD11b+CD11c–CD45low microglia purified from the inflamed CNS were found to be largely incapable of activating either naïve or effector T cells.